Walnut fruit: Impact of ethylene assisted hulling on in vitro antioxidant activity, polyphenols, PUFAs, amino acids and sensory attributes. (15th March 2023) - Farooq, Aiman; Hussain, Syed Zameer; Bhat, Tashooq Ahmad; Naseer, Bazila; Shafi, Fauzia
Highlights: Spraying method resulted in maximum retention of polyunsaturated fatty acids. Spraying method had the most pleasant odor. Spraying method presented the higher antioxidant activities and sweet tastes. Abstract: The effects of three different hulling methods wiz natural heaping/traditional (T1), steeping (T2), and spraying (T3), on moisture, colour, fat, free amino acids, fatty acids, antioxidant activities, flavonoids, tannins, total phenolic content, and organoleptic qualities of walnut kernels were examined in this study. The kernels extracted from walnuts subjected to T3 method recorded significantly (p ≤ 0.05) highest DPPH inhibition (68.61 %), ABTS (54.56 %inhibition) and FRAP (0.106 μM trolox/100 g); flavonoids (1993.08 mg QE/100 g), tannin content (0.312 %) and phenols (0.736 mg GAE/g) compared to T1 and T2. Walnut kernels of T3 treatment group were rated better in terms of taste (3.8), odour (3.6) and overall acceptability (3.78) Furthermore, walnut kernels obtained from T3 treatment group exhibited the highest percentage of unsaturated fatty acids (UFAs) and sweet free amino acids. The outcome of the present study offers a fresh viewpoint regarding the hulling processes of green walnuts to meet the quality requirements of walnut kernels.